Entrevista com atores institucionais: Prof. Dr. Paulo Eduardo Moreira Rodrigues da Silva - Sandra Regina de Angelis Terra; Elaine Aparecida de Carvalho Salcedo (Universidade Estadual de Campinas, 2015)
Entrevista com atores institucionais: Prof. Dr. Paulo Eduardo Moreira Rodrigues da Silva